2001
DOI: 10.1002/path.969
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR‐3 in adult angiogenesis

Abstract: Vascular endothelial growth factor receptor 3 (VEGFR-3, Flt-4), the receptor for vascular endothelial growth factors (VEGFs) C and D, is expressed on lymphatic endothelium and may play a role in lymphangiogenesis. In embryonic life, VEGFR-3 is essential for blood vessel development. The purpose of this study was to investigate whether VEGFR-3 is also involved in blood vessel angiogenesis in the adult. This was studied in human tissues showing angiogenesis and in a model of VEGF-A-induced iris neovascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
2
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 23 publications
8
102
2
5
Order By: Relevance
“…angiogenesis but is otherwise low in stable arteries (Gu et al, 2001;Witmer et al, 2001;Tammela et al, 2008). However, we found that its mRNA was readily detectable in the normal mouse aorta, and a reporter construct was up regulated at the inner curvature of the aortic arch that is exposed to disturbed shear stress.…”
Section: Vegfr3 Contributes To Shear Signaling In Vivomentioning
confidence: 64%
See 1 more Smart Citation
“…angiogenesis but is otherwise low in stable arteries (Gu et al, 2001;Witmer et al, 2001;Tammela et al, 2008). However, we found that its mRNA was readily detectable in the normal mouse aorta, and a reporter construct was up regulated at the inner curvature of the aortic arch that is exposed to disturbed shear stress.…”
Section: Vegfr3 Contributes To Shear Signaling In Vivomentioning
confidence: 64%
“…VEGFR3 is expressed in lymphatic endothelial cells (Karkkainen et al, 2000) and angiogenic endothelium (Kubo et al, 2000;Gu et al, 2001;Witmer et al, 2001; Tammela et al, Ncad and VEcad chimeras to identify the sequences required for shear stress mechanotransduction. This approach led to the surprising result that the TMD is the critical VEcad specific se quence.…”
Section: Vegfr3 Contributes To Shear Signaling In Vivomentioning
confidence: 99%
“…For example, the expression of VEGFR-3 is detectable in BECs before lymphatic sprouting, but after then is restricted to LECs, thus serving as an important LECsignature gene in normal tissues (Jeltsch et al 1997). However, abnormal expression of VEGFR-3 in BECs has been reported in various malignant tumors and granulation tissues (Partanen et al 1999;Valtola et al 1999;Witmer et al 2001;Nakamura et al 2003). Thus, VEGFR-3 expression in BECs was postulated to be a new microvascular progression marker that mediates lymphangiogenic factor-induced neovascularization (Clarijs et al 2002).…”
Section: Plasticity Of Lymphatic Endothelial Cell Fate-lymphatic Equimentioning
confidence: 99%
“…Air-dried serial cryostat sections (8 m thick) were fixed in cold acetone for 10 min and stained by an indirect immunoperoxidase procedure (Witmer et al 2001), using the following antibodies: monoclonal antibodies (MAb) Flt-19 (against VEGFR-1, dilution 1:400) and KDR-1 (against VEGFR-2, dilution 1:400) (Simon et al 1998), MAb 9D9F9 (against VEGFR-3, dilution 1:1500) (Lymboussaki et al 1998), and the anti-endothelial MAbs PAL-E (dilution 1:1000) (Schlingemann et al 1985) and EN-4 (against CD31; dilution 1:500) (Ruiter et al 1989). Flt-19 and KDR-1 were kindly provided by Dr. H.A.…”
Section: Light Microscopic Immunohistochemistrymentioning
confidence: 99%